2015
DOI: 10.1109/tmm.2015.2431915
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Synchronization of Mulsemedia Services

Abstract: Abstract-Multimediasynchronization involves a temporal relationship between audio and visual media components. The presentation of "in-sync" data streams is essential to achieve a natural impression, as "out-of-sync" effects are often associated with user quality of experience (QoE) decrease. Recently, multi-sensory media (mulsemedia) has been demonstrated to provide a highly immersive experience for its users. Unlike traditional multimedia, mulsemedia consists of other media types (i.e., haptic, olfaction, ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 46 publications
0
36
0
3
Order By: Relevance
“…Montagud et al extensively reviewed 19 emerging media applications that require inter-destination synchronization from the level of "very high" (10 µs-10 ms) to "low" (500 ms-2000 ms) [22]. In a recent study on perceived synchronization of multi-sensory media, Yuan et al concluded that users may tolerate haptic and air-flow media being one to three seconds behind corresponding video content [39]. A game-with-a-purpose (GWAP) approach was also taken to measure the lower asynchronism (non-synchronicity) as 400 ms for a social TV scenario [26].…”
Section: Use Case and Related Workmentioning
confidence: 99%
“…Montagud et al extensively reviewed 19 emerging media applications that require inter-destination synchronization from the level of "very high" (10 µs-10 ms) to "low" (500 ms-2000 ms) [22]. In a recent study on perceived synchronization of multi-sensory media, Yuan et al concluded that users may tolerate haptic and air-flow media being one to three seconds behind corresponding video content [39]. A game-with-a-purpose (GWAP) approach was also taken to measure the lower asynchronism (non-synchronicity) as 400 ms for a social TV scenario [26].…”
Section: Use Case and Related Workmentioning
confidence: 99%
“…So, many VR applications have been restricted to operate with local video information, although synthesized video could be generated online from delivered abstract representations. Moreover, the synchronized presentations of all multimedia data streams should not be forgotten [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on QoE performance when considering additional sensory objects to classical video services are provided in [17]. The synchronization between multiple media components such as 2D video, haptic and airflow is analyzed in [18] by measuring the Mean Opinion Score (MOS) for the perceived sense of relevance, reality, distraction, annoyance and enjoyment. In [19], the user perceived QoE denotes that the mulsemedia objects can only partially mask the decrease in movie quality.…”
Section: Related Workmentioning
confidence: 99%